African Youth in Mind – Protocol of a Pilot feasibility trial of a brief psychological Intervention for older adolescents with depression delivered through senior high schools in Navrongo, Ghana - Rebecca Jopling; Dzifa Attah; Melanie Abas; Kenneth Setorwu Adde; Kimberley Goldsmith; Tarisai Bere; Primrose Nyamayaro; Raymond Akawire Aborigo; Barbara Barrett; Lucy Owusu; Franklin Glozah; Anthony Akanlu; et al. (PLoS ONE, 2025)
In Ghana, one in three adolescents are at risk of experiencing depression. However, access to treatment is limited due to the poor integration of mental health services into primary healthcare systems. Evidence-based interventions, especially psychological therapies and antidepressant medication, can restore health and functioning for depressed youth. Ghana currently runs a policy of free Senior High Secondary Education and aims to implement a national adolescent health policy. However, the mental health component is poorly developed. Our formative research informed the adaptation of a 6-session psychological intervention for depression, suitable for school-going youth aged 15-18 in Ghana. The aim of this study is to conduct a pilot trial of this ‘African Youth in Mind’ (Y-MIND) intervention, to answer questions of feasibility and acceptability before evaluating the intervention in a larger definitive trial. The Y-MIND intervention blends evidence-based problem-solving therapy with behavioural activation and psychoeducation. The intervention will be delivered by trained and supervised guidance and counselling coordinators. The study is a parallel arm cluster randomised controlled pilot trial. Six senior high schools will each be randomly allocated 2:1 to either the intervention condition or enhanced usual care (EUC). 60 adolescents aged 15 to 18 years in senior high schools who have scored have scored 10 or more on the locally validated Patient Health Questionnaire-9 (PHQ-9) will be randomised. The feasibility, acceptability and appropriateness of the intervention will be assessed using short quantitative measures, and qualitative interviews with adolescents and guidance and counselling coordinators. Symptoms of depression will be measured at 5 months post baseline assessment. Outcomes for anxiety, fidelity to the intervention, and cost effectiveness evaluation will also be collected. This will be the first feasibility trial of a task-shifted psychological treatment (Y-MIND) for adolescents with depression delivered by Guidance and Counselling Coordinators in high schools in any African country. Clinicaltrials.gov NCT06740084.